Fractionation and subfunctionalization following genome duplications: mechanisms that drive gene content and their consequences. (December 2015) - Freeling, Michael; Scanlon, Michael J; Fowler, John E
Abstract : A gene's duplication relaxes selection. Loss of duplicate, low-function DNA (fractionation) sometimes follows, mostly by deletion in plants, but mostly via the pseudogene pathway in fish and other clades with smaller population sizes. Subfunctionalization — the founding term of the Xfunctionalization lexicon — while not the general cause of differences in duplicate gene retention, becomes primary as the number of a gene's cis — regulatory sites increases. Balanced gene drive explains retention for the average gene. Both maintenance-of-balance and subfunctionalization drive gene content nonrandomly, and currently fall outside of our accepted Theory of Evolution. The 'typical' mutation encountered by a gene duplicate is not a neutral loss-of-function; dominant mutations (Muller's lexicon; these are not neutral) abound, and confoundX functionalization terms like 'neofunctionalization'. Confusion of words may cause confusion of thought. As with many plants, fish tetraploidies provide a higher throughput surrogate-genetic method to infer function from human and other vertebrate ENCODE-like regulatory sites.